Beyond co-pays and out-of-pocket costs: perceptions of health-related financial burden in managing asthma among African American women. (December 2014) - Patel, Minal R.; Nelson, Belinda W.; Id-Deen, Effat; Caldwell, Cleopatra H.
Abstract Objective: The purpose of this study was to define perceptions of health-related financial burden based on the views of individuals who report these perceptions through qualitative approaches. Methods: Four focus groups were conducted in Southeast Michigan with 26 African American women with asthma, recruited based on maximum variation sampling procedures. A semi-structured interview was employed by facilitators. Coded transcripts were analyzed for themes regarding dimensions of the meaning of financial burden. Results: Major domains of financial burden identified included (1) high out-of-pocket expenses; (2) lost wages from exacerbations, inability to maintain a stable job and stress from making decisions about taking a sick day or coming to work; (3) transport costs; (4) both costs and stress of managing insurance eligibility and correcting erroneous bills. Conclusion: Greater awareness of factors that add to perceptions of financial burden might better equip researchers to develop interventions to help care teams manage such concerns with their patients.